DC transformer based hybrid AC/DC microgrid and DC distribution network - Zhang, Tengfei (2018)
The isolated bidirectional DC/DC converter has many advantageous characters such as high efficiency, high power density and good stability. It can be used to connect AC bus and DC bus by cooperating with bidirectional interlinking converter (BIC). It can also eliminate the gap between DC buses from different voltage levels. It has been widely applied in electric vehicles, energy storage systems power, quality regulation, renewable energy power generation, etc. In this dissertation, a symmetrical CLLC-type resonant dual active bridge (DAB) converter is used to realize the DC transformer topology. The dissertation focuses on 3 main parts. The first part is the transmission power analysis and fundamental control theory for DC transformer. The second part is mainly about the implementation of DCT control strategies in different modes based on DSP programming. The last part presents the verification experiments carried out both in hybrid AC/DC micro-grid and in DC distribution network.